Significant population genetic structuring in Rhyzopertha dominica across Turkey: Biogeographic and practical implications. (January 2020) - McCulloch, G.A.; Gurdasani, K.; Kocak, E.; Daglish, G.J.; Walter, G.H.
Abstract: Rhyzopertha dominica is a key pest of stored grain. Understanding the movement of this beetle on broad geographic scales is crucial, particularly when developing strategies to prevent the spread of phosphine resistance. We assessed population genetic structuring in this pest across Turkey, using a combination of mitochondrial (cytochrome oxidase I) and microsatellite markers. In addition, we screened samples for Wolbachia, as this endosymbiont has previously been suggested to be associated with low mitochondrial genetic diversity in this beetle. Mitochondrial genetic diversity was low, with only six haplotypes identified. The genetic diversity was, however, substantially higher than that previously found in Australia or India, suggesting that R. dominica may have originated in the Middle East. Wolbachia were detected only at a single site, indicating they are not impacting the mitochondrial genetic diversity of R. dominica across Turkey. Microsatellite markers indicated there is significant geographic genetic structuring across Turkey, even among sites less than 100 km apart, suggesting there is little movement of beetles across regions within the country. This contrasts with the significantly higher levels of gene-flow found in Australia and the United States. We suggest that the limited movement of beetles across Turkey may be due to a combination of the historically localised agricultural practices (which limits anthropogenic movement among regions), and the mountainous landscape (which limits active flight among regions). Our results demonstrate that the movement of stored product pests may differ significantly across studies conducted in different countries. As a consequence, phosphine resistance management strategies must incorporate region specific information on the extent of beetle movement. Highlights: We assessed population genetic structuring in Rhyzopertha dominica across Turkey. COI diversity was higher than in other countries, suggesting a Middle Eastern origin for R. dominica . Significant geographic genetic structure was evident, indicating limited gene flow across Turkey. Our results contrast with limited genetic structure typically reported in this pest. Inferences made about movement of stored product pests may not apply across different regions.